Design and Development of Vision Based Blockage Clearance Robot for Sewer Pipes - Krishna Prasad Nesaian; M. Bala Karthikeyan (IAES International Journal of Robotics and Automation (IJRA), 2012)
Robotic technology is one of the advanced technologies, which is capable of completing tasks at situations where humans are unable to reach, see or survive. The underground sewer pipelines are the major tools for the transportation of effluent water. A lot of troubles caused by blockage in sewer pipe will lead to overflow of effluent water, sanitation problems. So robotic vehicle that is capable of traveling at underneath effluent water determining blockage using ultrasonic sensors and clearing by means of drilling mechanism is done. In addition to that wireless camera is fixed which acts as a robot vision by which we can monitor video and capture images using MATLAB tool. Thus in this project a prototype model of underground sewer pipe blockage clearance robot with drilling type will be developedDOI: http://dx.doi.org/10.11591/ijra.v1i1.192